Goggle-eyes - Fine, Anne. (London : Puffin books, 1990)
Kitty Killin is not only the worlds greateststory teller when it comes to unwanted boyfriends. That's why she is sent to the dark privacy of the lost property cupboardto talk to her about her problems. She tells the story of her mum and her mums unwanted boyfriend. She give him the worst time of his life so that he breaks up with her mum.
5-8.
Keywords: Mother-daughter relationship -- Fiction